A systematic review of resonant voice therapy. (2nd January 2017) - Yiu, Edwin M.-L.; Lo, Marco C.M.; Barrett, Elizabeth A.
Abstract: Purpose : The purpose of this study is to systematically review the literature on resonant voice therapy and to evaluate the level of evidence on the effectiveness of using resonant voice therapy in treating dysphonia. Method : Refereed journal papers from 1974 to 2014 were retrieved and reviewed by two independent reviewers using the keywords "Humming, Resonance, Resonant Voice, Semi-occluded or closed tube phonation" using available database systems. Quality of evidence was evaluated by using the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Result : Thirteen papers met the search criteria. Nine papers were selected by the two reviewers. Two of the papers were randomised-controlled studies and the other seven were observational studies. At least four types of resonant voice therapies were described. They included the Lessac-Madsen Resonant Voice Therapy, Y-Buzz, Resonance Therapy and Humming. The overall level of quality of evidence was graded as "moderate". Conclusion : There were limited studies that investigated the effectiveness of resonant voice therapy. Most studies were small-scale uncontrolled observational studies with the inclusion of only small samples or specific populations. There is clearly a need for more large-scale randomised controlled studies with a wider range of populations to provide further evidence on the effectiveness of resonant voice training for different populations.